Religious Moderation in the perspective of the Ministry of Religion and its Implementation on Islamic Education book in Senior High School - Weeke Alfulana, Meila (Green Publisher Indonesia, 2023)
Indonesia isa plural country consisting of several religions. Religious differences often create friction and conflict due to claims of religious interpretation with theextreme hood. The Ministry of Religious Affairs of the Republic of Indonesia offered a middle-ground religious solution. Arti, bera gama believes his beliefs by not being fanatical and not judging the beliefs of others. This middle ground is called religious moderation. Religious moderation according to Oman Fathurrahman is defined as reducing violence or avoiding extremes. Thepurpose of holding this study is to examine how the implementation of religious moderation in PAI subjects in high school. The implementation of moderation is analyzed based on the module on strengthening religious moderation published by the Ministry of Religious Affairs of the Republic of Indonesia. This research uses qualitative proximity to data collection techniquesin the form of literature studies or literature studies. This research resulted in moderationand the perspective of the Ministry of Religion of the Republic of Indonesia upholding one's perspective, attitudes and practices in religion. Its implementation in PAI can realize the goal of Islamic Religious Education as a whole, namely becoming a kamil person. As one of the main teachings of Islam knows, is not to insult others